Activity and time budget of Tufted Ducks on Swiss lakes during winter - Pedroli, Jean-Carlo (Wildfowl, 1982)
Since the invasion of Lake Neuchtel by Dreissena polymorpha in 1967, the wintering population of Tufted Duck Aythya fuligula has greatly increased. From 1975 to 1979 the author studied the activity and movements of these birds with a telescope and, at night, with a night vision scope, the complete daily activity of the ducks was determined. Feeding occurs mainly during the night, resting during the day. The same result was obtained on Lake Geneva, which is also colonized by D. polymorpha, and on the Niederried reservoir, not yet colonized. On Lake Neuchtel, the feeding area with the least disturbance was occupied first, and had, on the whole, the greatest number of wintering ducks. The movement of ducks towards the other feeding places was caused by night disturbance during the feeding. There were some similarities of behaviour between these and other species of wintering ducks, such as the diurnal resting and nocturnal feeding and the collective restlessness at dusk and dawn. Nocturnal feeding activity was not confirmed as being due to diurnal predation pressure.